Metafora dan Hiperbola dalam Novel Laskar Pelangi Karya Andrea Hirata: Kajian Stilistika - Intang, Ambo; Jufri, Jufri (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to describe the form and function of figurative language styles of metaphor and hyperbole in the novel Laskar Pelangi by Andrea Hirata through a stylistic approach. The background of this study is the lack of research that specifically discusses the role of figurative language styles in a stylistic perspective. The research method uses qualitative descriptive with stylistic analysis techniques according to Leech & Short, including identification, classification, and interpretation of aesthetic functions and linguistic meanings. The results show that metaphors in this novel are used to build character traits, describe social struggles, and convey criticism in a subtle but sharp manner. Meanwhile, hyperbole is used to express emotional intensity, strengthen dramatic nuances, and highlight the passion and dreams of the main character. These two styles of language have significant stylistic functions in creating foregrounding effects, strengthening aesthetic power, and deepening moral and social messages in the narrative. These findings emphasize the importance of metaphor and hyperbole as stylistic strategies in enriching literary expression and shaping Andrea Hirata's writing style identity. AbstrakPenelitian ini bertujuan mendeskripsikan bentuk dan fungsi gaya bahasa metafora dan hiperbola dalam novel Laskar Pelangi karya Andrea Hirata melalui pendekatan stilistika. Latar belakang penelitian ini adalah minimnya penelitian yang secara khusus membahas peran gaya bahasa figuratif dalam perspektif stilistika. Metode penelitian menggunakan deskriptif kualitatif dengan teknik analisis stilistika menurut Leech & Short, meliputi identifikasi, klasifikasi, dan interpretasi fungsi estetik serta makna kebahasaan. Hasil penelitian menunjukkan bahwa metafora dalam novel ini digunakan untuk membangun karakter tokoh, menggambarkan perjuangan sosial, dan menyampaikan kritik secara halus namun tajam. Sementara itu, hiperbola digunakan untuk mengekspresikan intensitas emosi, memperkuat nuansa dramatik, dan menonjolkan semangat serta impian tokoh utama. Kedua gaya bahasa ini memiliki fungsi stilistik yang signifikan dalam menciptakan efek foregrounding, memperkuat daya estetika, serta memperdalam pesan moral dan sosial dalam narasi. Temuan ini menegaskan pentingnya metafora dan hiperbola sebagai strategi stilistika dalam memperkaya ekspresi sastra dan membentuk identitas gaya penulisan Andrea Hirata.